Salidroside Promotes the Pathological α-Synuclein Clearance Through Ubiquitin-Proteasome System in SH-SY5Y Cells - Li, Tao; Feng, Yang; Yang, Ruixin; Wu, Leitao; Li, Ruru; Huang, Lu; Yang, Qian; Chen, Jianzong (Frontiers in Pharmacology, 2018)
Parkinson’s disease (PD) is characterized by the loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNc) and the presence of Lewy bodies (LBs) in the surviving SNc neurons. LBs formation is caused by the accumulation of α-synuclein (α-syn) or phosphorylated α-syn at serine-129 (pSer129-α-syn), which is implicated in the pathological progression of PD. Salidroside (Sal), the main active ingredient of the root of Rhodiola rosea L., has been reported to have potent neuroprotective properties in our previous investigations. Here we investigated the effects of Sal on 6-OHDA and overexpresssion of WT/A30P-α-syn-induced pathological α-syn increase and the mechanism behind it in SH-SY5Y cells. We found Sal displays neuroprotective effects against 6-hydroxydopamine-(6-OHDA) and overexpression of WT/A30P-α-syn induced cytotoxicity. Sal decreased the pSer129-α-syn level mainly by maintaining the normal function of Ubiquitin-proteasome system (UPS). Furthermore, Sal promoted the clearance of α-syn and protected the cell viability mainly through recovered the 20S proteasome activity in WT/A30P-α-syn-transfected cells. These data provide new mechanistic insights into the neuroprotective effects of Sal and Sal may be a promising therapy to slow neurodegeneration in PD.